(untitled) (Bangladesh Journal of Medical Science, 2020)
Objectives: Calreticulin (CALR) and CCAAT/enhancer binding protein (C/EBP) alpha (CEBPA) are two important multifunctional proteins which play different roles in regulation of hematopoiesis. Expressional changes of these genes were related to the malignancy. Methods: The present study aimed to investigate the expression levels of CALR and CEBPA genes in 96 de novo AML patients compared to 18 normal people as the control group through the Real-Time-PCR. Results: Results of the present study revealed that the expression of these genes was significantly higher in patients with AML than the normal group (P <0.0001). Furthermore, there was a significant and positive correlation between CALR and CEBPA (P= 0.001 and r= 0.348). Discussion: Higher level of CALR expression was expected, but the overexpression of CEBPA was on the contrary to its well-known role in the myeloid maturation. Based on the studies, CALR probably played roles in the expression of oncogenic CEBPA and it repressed the CEBPA translation in tumor suppressor gene (TSG). Conclusion: The present study first indicated the over-expression of CALR in AML patients and compared it with the healthy normal control group and also found a positive relationship between CALR and CEBPA expression in the AML patients. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.730-736